Enhancement of the mechanical properties of lysine-containing peptide-based supramolecular hydrogels by chemical cross-linking. Issue 37 (8th September 2021) - Marshall, Libby J.; Matsarskaia, Olga; Schweins, Ralf; Adams, Dave J.
Abstract : Cross-linking lysine-containing peptide-based gelators with glutaraldehyde allows tuning of the final gel mechanical properties. Abstract : Exposure of lysine-containing peptide-based gelators to the cross-linking agent glutaraldehyde allows tuning of gel mechanical properties. The effect of cross-linking depends on the position of the lysine residue in the peptide chain, the concentration of gelator and the conditions under which cross-linking takes place. Through control of these factors, cross-linking leads to increased gel strength.